Reflections of an analogical romanist on legal training (online?) of the 21st century - Mentxaka, Rosa (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
The present pages aim to expose on the one hand, the role that roman law can have in the formation of the advanced jurist in the twenty-first century, as well as the challenges faced by the training of said jurist; consequently, the relationship between law and history, law and new technologies or global law are exposed. Addressing these challenges requires the interdisciplinary collaboration of all legal disciplines.